2010
DOI: 10.1007/s00296-010-1546-7
|View full text |Cite
|
Sign up to set email alerts
|

Cold and heat pattern of rheumatoid arthritis in traditional Chinese medicine: distinct molecular signatures indentified by microarray expression profiles in CD4-positive T cell

Abstract: The research is aimed to explore the distinct molecular signatures in discriminating the rheumatoid arthritis patients with traditional Chinese medicine (TCM) cold pattern and heat pattern. Twenty patients with typical TCM cold pattern and heat pattern were included. Microarray technology was used to reveal gene expression profiles in CD4+ T cells. The signal intensity of each expressed gene was globally normalized using the R statistics program. The ratio of cold pattern to heat pattern in patients with RA at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 41 publications
3
63
0
Order By: Relevance
“…The differential expression of IFI27 between patients is in line with earlier observations of interindividual differences in IFN type I response activity among RA patients (Chen et al, 2010).…”
Section: Cd4 T-lymphocytessupporting
confidence: 77%
“…The differential expression of IFI27 between patients is in line with earlier observations of interindividual differences in IFN type I response activity among RA patients (Chen et al, 2010).…”
Section: Cd4 T-lymphocytessupporting
confidence: 77%
“…From what has been mentioned above, we may conclude that differentially expressed proteins are all upregulated in the damp-heat group compared with the cold-damp group and control group, suggesting that RA patients with damp-heat impeding syndrome have severe inflammatory responses and high RA inflammatory activity. Previously, there have been some studies focusing on the biological mechanism of the damp-heat impeding/hot syndrome in RA patients, and their research indicated that the damp-heat impeding/hot syndrome and damp-cold impeding/cold syndrome may have a different inflammatory status [3,8]. Our study further found evidence to suggest that damp-heat impeding syndrome of RA have severe inflammatory responses and high RA inflammatory activity.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, modern omics technologies have been applied to investigate damp-heat impeding syndrome/ hot syndrome of RA. For example, hot syndrome of RA has been studied by using genomics technology [8] and metabolomics technology [9,10]. However, the biological basis of damp-heat impeding syndrome/hot syndrome of RA is rarely studied by using proteomics technology.…”
Section: Introductionmentioning
confidence: 99%
“…All the RA patients were diagnosed based on the American College of Rheumatology (ACR) criteria. Females were recruited according to the inclusion criteria in our previous study, 7 and those who had severe cardiovascular, lung, liver, kidney, hematologic, or mental disease and were pregnant, breast-feeding, or planning to become pregnant in the next 8 months were excluded.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…6,7 With the rapid development of systems biology, researchers have used genomics technology to explore differences in gene expression from the CD4+ T cells of RA cold and heat patients. 6,7 These studies have supplied the genomic basis to clarify the differentiation theory in TCM.…”
Section: Introductionmentioning
confidence: 99%